2019
DOI: 10.5152/turkpediatriars.2018.01819
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal effects of thyroid diseases in pregnancy and approach to the infant with increased TSH: Turkish Neonatal and Pediatric Endocrinology and Diabetes Societies consensus report

Abstract: Thyroid functions in the fetus and newborn carry importance in terms of the baby’s health and development of the central nervous system. Maternaliodine deficiency, exposure to iodine, thyroid diseases (Hashimoto thyroiditis, Graves’) and drugs used by the mother affect thyroid functions in the fetus. Reflections of these effects are observed immediately after delivery. Investigation of the mother in terms of thyroid diseases during pregnancy, recognition and appropriate assessment of the required conditions, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…In our study, rates of recall and CH were 5.34% and 0.33% among all neonates, regardless of maternal thyroid status. In Turkey, the prevalence of CH during our study period was high, at approximately 1/400 17 . The current high CH rates in Turkey can be explained by a significant iodine deficiency in pregnant women 22 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In our study, rates of recall and CH were 5.34% and 0.33% among all neonates, regardless of maternal thyroid status. In Turkey, the prevalence of CH during our study period was high, at approximately 1/400 17 . The current high CH rates in Turkey can be explained by a significant iodine deficiency in pregnant women 22 .…”
Section: Discussionmentioning
confidence: 72%
“…If the TSH value is higher than 20 mIU/L in the first heel blood sample or higher than 5.5 mIU/L in repeated heel blood samples, the newborn is referred to a neonatologist or pediatric endocrinologist for evaluation. The request for repeat blood sampling or referral to a specialist or pediatric endocrinologist is referred to as "recall" 16,17 .…”
Section: Congenital Hypothyroidism Screening Programmentioning
confidence: 99%
“…30 DÜNYA'DA DURUM 1990 yılına kadar yalnızca birkaç ülkede (Avustralya, Amerika Birleşik Devletleri (ABD), Kanada, İsviçre ve bazı İskandinav ülkeleri) iyot yeterli düzeydeydi. 31 37 Ülkemizde gebelerin iyot durumunu araştıran çalışmalar genellikle yerel ve küçük grupları kapsamaktadır. Anaforoğlu ve ark.…”
Section: çOcukluk Dönemi̇nde İyot Eksi̇kli̇ği̇ni̇n Sonuçlariunclassified
“…Some studies have reported that HT causes severe cardiac effusion or cardiac tamponade independently or synergistically with other disease [10]. Excessively high titer of TPOAb and TGAb may cross blood-fetal barrier and lead to antenatal and neonatal disorders in pregnant patients [11].…”
Section: Introductionmentioning
confidence: 99%